Iron-based mixed powders and iron-based sintered bodies for powder metallurgy
The mixed powder for powder metallurgy, featuring partially diffusion alloy steel powder with Mo, Cu, and Ni, addresses the challenge of achieving high tensile strength and impact resistance in iron-based sintered bodies, while maintaining cost-effectiveness and reducing mold wear.
Patent Information
- Application Number
- JP2022024201
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2022-02-18
- Publication Date
- 2025-04-22
- Estimated Expiration
- 2042-02-18
AI Technical Summary
Existing powder metallurgy techniques struggle to produce iron-based sintered bodies with tensile strengths above 1200 MPa and impact resistance while maintaining cost-effectiveness and reducing mold wear.
A mixed powder for powder metallurgy comprising partially diffusion alloy steel powder with Mo diffused on the surface of iron-based powder particles, combined with Cu and Ni powders, which enhances compressibility, strength, and impact resistance without requiring high molding pressures or expensive alloy elements.
The solution achieves a high-density sintered body with tensile strengths of 1200 MPa or more and impact values of 13J/cm², while maintaining low manufacturing costs and reducing mold wear, even at molding pressures below 600 MPa.
Smart Images

Figure 0007666359000001 
Figure 0007666359000002 
Figure 0007666359000003
Abstract
Description
[Technical field]
[0001] The present invention relates to an iron-based mixed powder for powder metallurgy, in particular to an iron-based mixed powder for powder metallurgy which has excellent compressibility as a powder and can give a sintered body having excellent strength and impact resistance, and also to an iron-based sintered body produced by using said iron-based mixed powder for powder metallurgy. [Background technology]
[0002] Powder metallurgy products are generally manufactured by mixing raw material powders, filling a die, pressurizing the mixture into a molded body, and then sintering the molded body. The sintered body obtained by sintering is further subjected to sizing and cutting as necessary. For example, when manufacturing iron-based powder metallurgy products, it is common to use a mixed powder obtained by adding alloy powders such as Cu powder and graphite powder and lubricants such as stearic acid and lithium stearate to an iron-based powder as the raw material powder.
[0003] Such powder metallurgy technology makes it possible to manufacture parts with complex shapes in a shape that is very close to the product shape (a so-called near net shape) with high dimensional accuracy, which can greatly reduce the cost required for cutting. Therefore, powder metallurgy products are used in many fields, and iron-based powder metallurgy products in particular are widely used as various mechanical parts and structural parts, including automobile parts, due to their excellent strength.
[0004] However, in recent years, there has been a demand for even higher strength in iron-based powder metallurgy products in order to make parts smaller and lighter.
[0005] To manufacture an iron-based sintered body with a tensile strength exceeding 1000 MPa, it is necessary to carry out a carburizing heat treatment or a bright heat treatment after sintering. In particular, to manufacture an iron-based sintered body with a tensile strength exceeding 1200 MPa, it is necessary to use an alloy powder containing 4 mass% of Ni, an expensive alloy element, and a molding pressure exceeding 600 MPa is required. This causes severe wear on the die, and there is a problem that not only the material cost but also the manufacturing cost is high. In addition, when manufacturing such high-strength sintered parts with a molding pressure of less than 600 MPa, sintering must be carried out at a high temperature exceeding 1200°C, which also causes a problem of high manufacturing costs.
[0006] In the manufacturing process of general powder metallurgy products, sintering is performed using a continuous sintering furnace called a belt furnace. In a belt furnace, sintering is performed continuously while parts are transported on a mesh belt, which has the advantages of excellent productivity and low running costs. However, since the sintering temperature in a belt furnace is at most about 1150°C, sintering at high temperatures exceeding the above-mentioned 1200°C requires the use of a tray pusher furnace, which is less productive. In addition, when sintering at such high temperatures, there is also the problem that the furnace body is subject to severe wear and tear, resulting in high running costs.
[0007] In light of the above, various studies have been conducted to obtain high-strength sintered parts using inexpensive processes. Among them, many methods have been proposed to improve the strength of sintered bodies by adding alloy elements that improve hardenability to iron-based powders.
[0008] For example, Patent Document 1 proposes an alloy steel powder containing at least one of Mo: 1.5 to 2.0 mass % and W: 3.0 to 20 mass % as a prealloy.
[0009] Moreover, Patent Document 2 proposes an alloy steel powder in which Mo: 0.2 to 1.5% and Mn: 0.05 to 0.25% are pre-alloyed by weight.
[0010] Patent Document 3 proposes an alloy steel powder in which Cu and Ni are diffused and attached in the form of powder to the surface of iron powder containing 0.1 to 1.0 mass % Mo as a prealloy.
[0011] In Patent Document 4, an alloy steel powder containing 0.2 to 1.5 mass% Mo and a ferromagnetic powder having an average particle size of 25 μm or less and a specific surface area of 0.30 m are used. 2 / g or more of iron-based mixed powder for powder metallurgy has been proposed.
[0012] Patent Document 5 proposes an iron-based mixed powder for powder metallurgy, which contains a pre-alloyed steel powder in which Mo, Cu, and Ni are pre-alloyed, and graphite powder. [Prior art documents] [Patent documents]
[0013] [Patent Document 1] Japanese Patent Application Publication No. 01-142002 [Patent Document 2] Japanese Patent Application Publication No. 61-295302 [Patent Document 3] Japanese Patent Publication No. 59-215401 [Patent Document 4] International Publication No. 2020 / 202805 [Patent Document 5] JP 2018-123412 A Summary of the Invention [Problem to be solved by the invention]
[0014] However, it has been found that the conventional techniques proposed in Patent Documents 1 to 5 have the following problems.
[0015] That is, in the alloy steel powder proposed in Patent Document 1, the addition of Mo or W, which is a ferrite stabilizing element, forms an α single phase with a high self-diffusion rate of Fe, and as a result, sintering can be promoted. However, since the amount of Mo added in this method is relatively large, the alloy steel powder has low compressibility and cannot obtain a high compaction density.
[0016] In addition, a decrease in density tends to decrease the impact resistance of the sintered body. As described above, powder metallurgy products are used for various mechanical and structural parts, including automotive parts, and therefore are required to have excellent impact resistance.
[0017] In addition, the alloy steel powder proposed in Patent Document 2 does not have a single α phase because the Mo content is 1.5 mass% or less. Therefore, the sintering between particles is not promoted at the sintering temperature (1120 to 1140°C) of a commonly used mesh belt furnace, and the strength of the sintered neck portion is insufficient. In addition, in Patent Document 2, Mn is added as a pre-alloy element, but if the amount of Mn added is increased to improve hardenability, the compressibility of the powder decreases, and therefore a sufficient strength improvement effect cannot be obtained.
[0018] In the alloy steel powder proposed in Patent Document 3, Mo is pre-alloyed and Cu and Ni are diffused and attached, thereby achieving both compressibility during powder compaction and strength of the sintered member. However, as with the alloy steel powder in Patent Document 2, the sinterability of iron powder pre-alloyed with Mo is not good, so there is a limit to the improvement of tensile strength and fatigue strength.
[0019] With the mixed powder proposed in Patent Document 4, high-strength sintered parts can be obtained by sintering using a normal belt furnace and carburizing, quenching, and tempering. However, since the compressibility of the mixed powder is equivalent to that of general iron-based alloy powders, molding at high pressures of 688 MPa is necessary to obtain high tensile strength, which causes significant wear on the mold.
[0020] The mixed powder proposed in Patent Document 5 can produce a sintered body having a tensile strength of 1,300 MPa or more. However, as in Patent Document 4, the mixed powder requires high pressure molding at 690 MPa, which causes significant wear on the mold.
[0021] The present invention has been made in view of the above circumstances, and provides a molded article having excellent compressibility and a tensile strength of 1200 MPa or more and an impact value of 13 J / cm even in a general manufacturing process with a molding pressure of less than 600 MPa. 2 The object of the present invention is to provide an iron-based mixed powder for powder metallurgy capable of producing a sintered body having the above-mentioned excellent impact resistance. Here, compressibility refers to the ease of compression when the mixed powder is filled into a die and pressure-molded. As an index of the compressibility, the density of a molded body obtained when molded at a predetermined pressure can be used, and the higher the density, the better the compressibility.
[0022] Another object of the present invention is to provide an iron-based sintered body using the iron-based mixed powder for powder metallurgy. [Means for solving the problem]
[0023] The present invention has been made to solve the above problems, and has the following gist and configuration.
[0024] 1. An iron-based mixed powder for powder metallurgy, comprising a partially-diffused alloyed steel powder in which Mo is diffused and attached to the particle surface of the iron-based powder, and an alloying metal powder, The iron-based powder is Mn: 0.04 mass% or more and 0.15 mass% or less, Si: 0.01% by mass or more and 0.10% by mass or less, and The remainder is Fe and unavoidable impurities. The Mo content in the partially diffused alloyed steel powder is 0.20% by mass or more and 1.5% by mass or less, The apparent density of the partially diffused alloyed steel powder is 2.8 g / cm 3 More than 3.6g / cm 3 is as follows: The alloying metal powder has an apparent density of 0.5 to 2.0 g / cm 3 Cu powder, apparent density: 0.5~2.0g / cm 3 and / or with respect to the total mass of the partially diffused alloyed steel powder and the alloying metal powder, The amount of Cu powder added is 0 to 3.0 mass %, The amount of the Ni powder added is 0 to 3.0 mass%, and The iron-based mixed powder for powder metallurgy, wherein the total amount of the Cu powder and the Ni powder is 0.5 mass % or more.
[0025] 2. The iron-based mixed powder for powder metallurgy according to the above item 1, wherein the ratio of the mass of the Ni powder to the total mass of the Cu powder and the Ni powder is 0.8 or less.
[0026] 3. An iron-based sintered body obtained by carburizing, quenching and tempering a sintered body using the iron-based mixed powder for powder metallurgy described in 1 or 2 above. Effect of the Invention
[0027] The iron-based mixed powder for powder metallurgy of the present invention has excellent compressibility, and can produce a sintered body with high density. Moreover, the iron-based mixed powder for powder metallurgy of the present invention can produce a sintered body having both high tensile strength and excellent impact resistance, even in a general manufacturing process in which the molding pressure is less than 600 MPa. In addition, the iron-based mixed powder for powder metallurgy of the present invention does not contain Ni, or even if it does contain Ni, the amount of Ni added is 3.0 mass % or less, so that it is inexpensive and has the above-mentioned excellent properties. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0028] Hereinafter, the embodiments of the present invention will be described in detail. Note that the following description shows preferred embodiments of the present invention, and the present invention is not limited to the following description. Furthermore, the unit "%" regarding the composition of components represents "% by mass" unless otherwise specified.
[0029] In one embodiment of the present invention, the iron-based mixed powder for powder metallurgy (hereinafter, sometimes simply referred to as the mixed powder) is composed of a partially diffused alloyed steel powder and an alloying metal powder. Here, the term "iron-based mixed powder" refers to a mixed powder in which the ratio of the mass of Fe contained in the mixed powder to the total mass of the partially diffused alloyed steel powder and the alloying metal powder is 50% or more.
[0030] The partially diffused alloyed steel powder and the alloying metal powder will be described below.
[0031] [Partially diffused alloyed steel powder] The partially diffused alloyed steel powder (hereinafter also referred to as "alloy steel powder") used is a partially diffused alloyed steel powder in which Mo is diffused and attached to the particle surfaces of an iron-based powder. Here, the "iron-based powder" refers to a powder in which the mass ratio of Fe contained in the powder is 50% or more.
[0032] The iron-based powder has a composition consisting of 0.04% by mass or more and 0.15% by mass or less of Mn, 0.01% by mass or more and 0.10% by mass or less of Si, and the balance being Fe and unavoidable impurities. The reasons for these limitations are explained below.
[0033] Mn: 0.04 to 0.15% Mn is an element contained as an inevitable impurity in iron-based powder. If the Mn content exceeds 0.15%, the amount of Mn oxide generated increases. Mn oxide not only reduces the compressibility of the iron-based mixed powder for powder metallurgy, but also serves as the starting point of fracture inside the sintered body, thereby reducing the strength of the sintered body. Therefore, the Mn content is set to 0.15% or less, preferably 0.10% or less. On the other hand, from the viewpoint of improving the compressibility, a low Mn content is desirable, but excessive reduction leads to an increase in the time required for Mn removal treatment and therefore an increase in manufacturing costs. Therefore, the Mn content is set to 0.04% or more.
[0034] Silicon: 0.01 to 0.10% Si is an element contained in iron-based powder as an inevitable impurity. If the Si content exceeds 0.10%, the amount of Si oxide generated increases. Si oxide not only reduces the compressibility of the iron-based mixed powder for powder metallurgy, but also serves as the starting point of fracture inside the sintered body, thereby reducing the strength of the sintered body. Therefore, the Si content is set to 0.10% or less, preferably 0.05% or less. On the other hand, from the viewpoint of improving the compressibility, a low Si content is desirable, but excessive reduction leads to an increase in the time required for the Si removal process and therefore an increase in manufacturing costs. Therefore, the Si content is set to 0.01% or more.
[0035] Although not particularly limited, the iron-based powder is preferably an atomized powder. The atomized powder may be either a gas atomized powder or a water atomized powder, but is more preferably a water atomized powder. The atomized powder is preferably one that has been subjected to a treatment to reduce C and O by heating in a reducing atmosphere (e.g., a hydrogen atmosphere) after atomization. However, as the atomized powder, it is also possible to use an iron-based powder that has not been subjected to such heat treatment as it is atomized.
[0036] Mo is diffused and attached to the particle surfaces of the iron-based powder. In the present invention, the Mo content in the partially diffused alloyed steel powder is set to 0.20% or more and 1.5% or less. The reason for this limitation will be explained below.
[0037] Mo: 0.20~1.5% Mo is an element that improves hardenability, and a sufficient hardenability improvement effect can be obtained by adding a small amount compared to Ni. If the Mo content in the partially diffused alloyed steel powder is less than 0.20%, the strength improvement effect of Mo becomes insufficient. Therefore, the Mo content in the partially diffused alloyed steel powder is set to 0.20% or more, preferably 0.40% or more. On the other hand, if the Mo content exceeds 1.5%, the effect of Mo in improving the strength of the sintered body becomes saturated, and the compressibility of the alloyed steel powder decreases, making the molding die more likely to wear. Therefore, the Mo content in the partially diffused alloyed steel powder is set to 1.5% or less, preferably 1.0% or less.
[0038] In this way, the present invention uses a partially diffused alloyed steel powder in which 0.20 to 1.5% of Mo is diffused and attached to the particle surfaces of the iron-based powder having the above-mentioned composition. Therefore, the partially diffused alloyed steel powder in one embodiment of the present invention can be said to have a composition that contains Mn derived from the iron-based powder, Si derived from the iron-based powder, and diffusion-adhered Mo, with the balance being Fe and unavoidable impurities.
[0039] The components and amounts contained as the unavoidable impurities are not particularly limited, but it is desirable to reduce them as much as possible. For example, when Ni is contained as the unavoidable impurity, Ni is a cause of increased material costs, so the Ni content is preferably 0.1% or less. In addition, the contents of C, O, P, S, and N as the unavoidable impurities are preferably within the following ranges. C: 0.01% or less O: 0.20% or less P:0.025% or less S: 0.025% or less N: 0.05% or less
[0040] The O content includes the amount of oxygen contained in oxides inevitably produced in the alloy steel powder. The total amount of elements other than those listed above contained as the inevitable impurities is preferably controlled to 0.01% or less.
[0041] Apparent density: 2.8~3.6g / cm 3 The apparent density of the partially diffused alloyed steel powder is an important property that has a large effect on the compressibility of the iron-based mixed powder for powder metallurgy, and is determined by properties such as the shape of each particle of the alloyed steel powder and the particle size distribution of the entire alloyed steel powder. The smaller the apparent density of the alloyed steel powder, the larger the volume of the iron-based mixed powder for powder metallurgy when filled into a die. As a result, the work hardening of the alloyed steel powder particles during press molding increases, inhibiting the plastic deformation of the particles, and lowering the density of the compact. This reduction in the density of the compact occurs when the apparent density of the partially diffused alloyed steel powder is 2.8 g / cm. 3This is particularly noticeable when the apparent density of the partially diffused alloyed steel powder is less than 2.8 g / cm. 3 More than 2.9 g / cm, preferably 2.9 g / cm 3 On the other hand, the apparent density of the partially diffused alloyed steel powder is 3.6 g / cm or more. 3 If the apparent density is higher, not only will the compressibility improvement effect saturate, but the strength of the compact will decrease, making the compact more likely to crack when it is removed from the die after press molding. In addition, if an attempt is made to increase the apparent density excessively, it will be necessary to carry out a process to make the shape of each particle closer to a sphere and a process to make the particle size distribution of the alloy steel powder a bimodal distribution, which will increase the manufacturing cost. For this reason, the apparent density of the alloy steel powder is set at 3.6 g / cm. 3 Less than 3.3 g / cm, preferably 3.3 g / cm 3 The apparent density can be measured in accordance with JIS Z 2504:2012.
[0042] The particle size of the partially diffused alloyed steel powder is not particularly limited and can be any particle size. From the viewpoint of ease of production, it is preferable that the average particle size of the partially diffused alloyed steel powder is 30 μm or more and 150 μm or less. By utilizing the water atomization method, alloyed steel powder having the above average particle size can be industrially produced at low cost. Here, the average particle size refers to the median diameter on a mass basis. The average particle size (D50) can be calculated by calculating the mass-based cumulative particle size distribution from the particle size distribution measured by the dry sieving method described in JIS-Z2510, and the particle size at which this value is 50% can be obtained by interpolation.
[0043] The method for producing the partially diffused alloyed steel powder is not particularly limited, but it can typically be produced by mixing the iron-based powder with a Mo raw material powder, and then maintaining the mixture at a high temperature to cause Mo to diffuse and adhere to the surface of the iron-based powder.
[0044] The Mo raw material powder is a powder that functions as a Mo source in the diffusion adhesion step described later. Any powder containing Mo as an element can be used as the Mo raw material powder. Therefore, any of metal Mo powder (powder consisting of Mo only), Mo alloy powder, and Mo compound powder can be used as the Mo raw material powder. For example, Fe-Mo (ferromolybdenum) powder and atomized Fe-Mo powder containing 5% or more Mo can be used as the Mo alloy powder. The atomized powder may be either gas atomized powder or water atomized powder. can be used. As the Mo compound powder, it is preferable to use Mo oxide because of ease of availability and ease of reduction reaction. These Mo raw material powders may be used alone or in combination.
[0045] The iron-based powder and the Mo raw material powder are mixed. During the mixing, the amounts of the iron-based powder and the Mo-containing powder are adjusted so that the Mo content in the final partially diffused alloyed steel powder is in the above-mentioned range. There is no particular limitation on the mixing method, and the mixing can be performed according to a conventional method using, for example, a Henschel mixer or a cone mixer. During the mixing, machine oil or the like can be added in the range of 0.1 mass % or less to improve adhesion between the iron-based powder and the Mo raw material powder.
[0046] The mixture is then heat-treated at 800 to 1000°C in a reducing atmosphere such as a hydrogen atmosphere to obtain an alloy steel powder in which Mo is diffused and attached as metallic Mo or a Mo-containing alloy. When an as-atomized iron-based powder containing a large amount of C and O is used as the iron-based powder, the C and O can be reduced by the heat treatment. It is preferable to use as-atomized iron powder for the iron-based powder, because C and O are reduced during the diffusion attachment treatment and the surface of the iron-based powder becomes active, making it easier for metallic Mo or a Mo-containing alloy to be attached by diffusion.
[0047] In the partially diffused alloyed steel powder obtained by the above procedure, at the site where the metal Mo or Mo-containing alloy contacts the iron-based powder, a part of the Mo in the metal Mo or Mo-containing alloy diffuses into the iron-based powder particles and adheres to the surface of the iron-based powder (hereinafter also referred to as diffusion adhesion). When Mo oxide powder is used as the Mo raw material powder, the Mo oxide is reduced to the form of metal Mo in the above heat treatment. As a result, a state in which the Mo content is partially increased by diffusion adhesion is obtained, similar to the case where the metal Mo powder or Mo-containing alloy powder is used as the Mo raw material powder.
[0048] In addition, when the heat treatment (including the diffusion adhesion treatment) is performed in this manner, the iron-based powder and metallic Mo or Mo-containing alloy are usually in a sintered state, so that the powder is crushed and classified to a desired particle size. In addition, it can be further annealed if necessary.
[0049] [Metal powder for alloys] Next, the alloying metal powder, which is another component of the iron-based mixed powder for powder metallurgy of the present invention, will be described. The iron-based mixed powder for powder metallurgy in one embodiment of the present invention has an apparent density of 0.5 to 2.0 g / cm as the alloying metal powder. 3 Cu powder, apparent density: 0.5~2.0g / cm 3 The alloying metal powder contains one or both of the above Ni powders. Here, the alloying metal powder has an apparent density of 0.5 to 2.0 g / cm 3 The Cu powder contained in the alloying metal powder has an apparent density of 0.5 to 2.0 g / cm 3 Similarly, the apparent density of alloying metal powder is 0.5 to 2.0 g / cm 3 The alloying metal powder contains Ni powder having an apparent density of 0.5 to 2.0 g / cm 3 This means that.
[0050] The amounts of Cu powder and Ni powder added must satisfy the following conditions. The amount of Cu powder added is 0 to 3.0 mass %. The amount of the Ni powder added is 0 to 3.0 mass %. The total amount of the Cu powder and the Ni powder added is 0.5 mass % or more. Here, the amount of Cu powder added is defined as the ratio of the mass of Cu powder having the apparent density to the total mass of the partially diffused alloyed steel powder and the alloying metal powder. Similarly, the amount of Ni powder added is defined as the ratio of the mass of Ni powder having the apparent density to the total mass of the partially diffused alloyed steel powder and the alloying metal powder. And the total amount added is defined as the sum of the amount of Cu powder added and the amount of Ni powder added.
[0051] The reasons for limiting the amounts of Cu powder and Ni powder added and the apparent density will be explained below.
[0052] Cu powder: 0~3.0% Cu is an element that improves hardenability, and is advantageous in that it is less expensive than Ni. However, in the manufacture of sintered bodies, sintering is generally performed at about 1130°C, but Cu melts at 1083°C to become liquid. The molten Cu expands the sintered body and reduces the density after sintering. If the amount of Cu powder added is more than 3.0%, the mechanical properties of the sintered body due to this density reduction will decrease significantly. Therefore, the amount of Cu powder added is 3.0% or less, preferably 2.0% or less. On the other hand, the lower limit of the amount of Cu powder added is not limited and may be 0%. However, from the viewpoint of enhancing the effect of Cu in improving hardenability, it is preferable to add Cu powder at 0.5% or more, and more preferably at 1.0% or more.
[0053] Apparent density of Cu powder: 0.5~2.0g / cm 3 The apparent density of Cu powder is a property that affects the powder characteristics and sintering characteristics of the mixed powder, and is determined by the size and shape of each Cu powder particle, the particle size distribution, and other properties of the Cu powder. 3 If the powder is less than 0.5 g / cm3, the powder flowability is deteriorated, and the height of the mixed powder filled in the die increases. In addition, the rearrangement of the alloy steel powder particles during press molding is hindered. As a result, the density of the compact decreases. Therefore, the apparent density of Cu powder is 0.5 g / cm3 or less. 3More than 1.0 g / cm, preferably 1.0 g / cm 3 On the other hand, the apparent density of Cu powder is 2.0 g / cm 3 If the temperature is higher, the sintering expansion during liquid phase sintering increases, resulting in a lower density. Therefore, the apparent density of Cu powder is 2.0 g / cm 3 Less than 1.5 g / cm 3 The apparent density can be measured in accordance with JIS Z 2504:2012.
[0054] Ni powder: 0~3.0% Ni powder has the effect of activating the sintering reaction of the alloy steel powder, refining the pores of the sintered body, and increasing the tensile strength and impact resistance of the sintered body. However, if the amount of Ni powder added is more than 3.0%, the amount of retained austenite in the sintered body increases significantly, and the strength of the sintered body decreases, and the raw material cost also increases. Therefore, the amount of Ni powder added is 3.0% or less, preferably 2.0% or less. On the other hand, the lower limit of the amount of Ni powder added is not limited and may be 0%. However, from the viewpoint of increasing the effect of activating the sintering reaction by Ni, the amount of Ni powder added is preferably 0.5% or more, and more preferably 1.0% or more.
[0055] The Ni powder is not particularly limited and any Ni powder can be used. Suitable Ni powders include Ni powder produced by reducing Ni oxide and carbonyl Ni powder produced by a thermal decomposition method.
[0056] Apparent density of Ni powder: 0.5~2.0g / cm 3 The apparent density of Ni powder is a property that affects the powder characteristics and sintering characteristics of the mixed powder, and is determined by the size and shape of each Ni powder particle, the particle size distribution, and other properties of the Ni powder. 3If the powder is less than 0.5 g / cm3, the powder flowability is deteriorated, and the volume of the mixed powder filled in the die increases significantly. In addition, the particle rearrangement of the alloy steel powder particles during press molding is inhibited. As a result, the density of the compact decreases. Therefore, the apparent density of Ni powder is 0.5 g / cm3 or less. 3 More than 1.0 g / cm, preferably 1.0 g / cm 3 On the other hand, the apparent density of the Ni powder is 2.0 g / cm 3 If the density is higher, the pores after sintering will become larger, which will reduce mechanical properties such as tensile strength and impact value. Therefore, the apparent density of Ni powder is 2.0 g / cm 3 Less than 1.5 g / cm 3 The apparent density can be measured in accordance with JIS Z 2504:2012.
[0057] Total amount of Cu powder and Ni powder added: 0.5% or more As described above, both Cu and Ni are elements that have the effect of improving the strength of the sintered body. In order to obtain a desired strength, the total amount of the Cu powder and the Ni powder needs to be 0.5% or more.
[0058] Ni powder mass ratio: 0.8 or less Cu-Ni alloy is known as a complete solid solution, and the melting point of Cu-Ni alloy rises from 1083°C for 100%Cu-0%Ni to 1455°C for 0%Cu-100%Ni depending on the Ni ratio. If the ratio of the mass of Ni powder to the total mass of Cu powder and Ni powder (hereinafter referred to as mass ratio) is 0.8 or less, the rise in melting point is suppressed, so that the liquid phase sintering of Cu powder is not inhibited, and the sintering promotion effect is increased. As a result, the strength and impact resistance can be further improved. Therefore, the mass ratio of Ni powder is preferably 0.8 or less, and more preferably 0.5 or less. The lower limit of the mass ratio of Ni powder is not particularly limited, but in order to obtain a higher sintered density, it is preferably 0.2 or more.
[0059] In another embodiment of the present invention, the alloying metal powder has an apparent density of substantially 0.5 to 2.0 g / cm 3Cu powder, apparent density: 0.5~2.0g / cm 3 The Ni powder may be one or both of the above.
[0060] In another embodiment of the present invention, the iron-based mixed powder for powder metallurgy may further contain other components in addition to the above-mentioned partially diffused alloyed steel powder and alloying metal powder, such as at least one of carbon powder, lubricant, and machinability improving powder.
[0061] Carbon powder The strength of the sintered body can be further improved by adding carbon powder. The carbon powder is not particularly limited and any carbon powder can be used. For example, one or both of graphite powder and carbon black can be used as the carbon powder. For the graphite powder, either natural graphite powder or artificial graphite powder can be used. When carbon powder is added, from the viewpoint of the strength improvement effect, the blending amount of the carbon powder is preferably 0.2 parts by mass or more per 100 parts by mass of the partially diffused alloyed steel powder and the alloying metal powder. On the other hand, the blending amount of the carbon powder is preferably 1.2 parts by mass or less per 100 parts by mass of the partially diffused alloyed steel powder and the alloying metal powder.
[0062] Lubricants By including a lubricant, it is possible to easily remove the molded body from the die. As the lubricant, any lubricant can be used without any particular limitation. As the lubricant, for example, one or both of a metal soap and an amide-based wax can be used. As the metal soap, for example, zinc stearate, lithium stearate, etc. can be mentioned. In addition, as the amide-based wax, for example, ethylene bis stearic acid amide can be mentioned.
[0063] The lubricant is preferably in powder form. When a lubricant is used, the amount of the lubricant added is preferably 0.3 to 1.0 parts by mass per 100 parts by mass of the partially diffused alloyed steel powder and the alloying metal powder combined.
[0064] ·Powder for improving machinability The machinability improving powder is not particularly limited and any machinability improving powder can be used. For example, one or both of MnS powder and oxide powder can be used as the machinability improving powder. When using the machinability improving powder, the amount of the machinability improving powder added is preferably 0.1 parts by mass or more and 0.7 parts by mass or less per 100 parts by mass of the total of the partially diffused alloy steel powder and the alloying metal powder.
[0065] [Method of manufacturing mixed powder] The iron-based mixed powder for powder metallurgy of the present invention can be produced by any method without any particular limitation. For example, it can be produced by mixing the alloying metal powder with the alloy steel powder so as to obtain the above-mentioned addition amount. The mixing can be carried out by any method. For example, it can be mixed using a V-type mixer, a double cone type mixer, a Henschel mixer, a Nauta mixer, or the like. During mixing, machine oil or the like may be added to prevent segregation of the Cu powder and Ni powder. Alternatively, the alloy steel powder and the alloying metal powder may be filled into a die for pressure molding so as to obtain the above-mentioned addition amount to obtain a mixed powder.
[0066] [Iron-based sintered body] The iron-based sintered body in one embodiment of the present invention is an iron-based sintered body obtained by carburizing, quenching, and tempering a sintered body using the above-mentioned iron-based mixed powder for powder metallurgy.
[0067] The iron-based sintered body in one embodiment of the present invention can be manufactured by pressurizing the iron-based mixed powder for powder metallurgy to obtain a molded body, sintering the molded body to obtain a sintered body, and then subjecting the sintered body to a heat treatment. Each step will be described below.
[0068] (Pressure molding) First, the iron-based mixed powder for powder metallurgy is pressure-molded into a desired shape to obtain a molded body. In the pressure molding, the iron-based mixed powder for powder metallurgy may be optionally mixed with auxiliary materials, lubricants, powders for improving machinability, etc. The method of the pressure molding is not particularly limited, and any method can be used, for example, a method in which the mixed powder is filled in a die and pressure molded. A lubricant can also be applied or attached to the die, and the amount of the lubricant in this case is preferably 0.3 parts by mass or more and 1.0 parts by mass or less with respect to 100 parts by mass of the total of the partially diffused alloyed steel powder and the alloying metal powder.
[0069] The pressure of the compaction can be 400 MPa or more and 1000 MPa or less. However, if the pressure exceeds 600 MPa, the wear of the die increases, and the manufacturing cost increases. Therefore, the pressure is preferably 400 to 600 MPa. According to the iron-based mixed powder for powder metallurgy of the present invention, for example, under the condition of a compaction pressure of 588 MPa, the density of the compact can be 7.10 g / cm. 3 It can be more than that.
[0070] (Sintering) The sintering method is not particularly limited, and can be performed by any method. The sintering temperature can be 1100°C or higher, preferably 1120°C or higher, from the viewpoint of sufficiently advancing the sintering. On the other hand, the higher the sintering temperature, the more uniform the distribution of Cu and Mo in the sintered body becomes, so the upper limit of the sintering temperature is not particularly limited, but from the viewpoint of suppressing the manufacturing cost, the sintering temperature is preferably 1250°C or lower, more preferably 1180°C or lower.
[0071] The sintering time can be 15 minutes or more and 50 minutes or less. Within this range, insufficient sintering and insufficient strength can be avoided, and manufacturing costs can be reduced. The cooling rate during cooling after sintering can be 20°C / min or more and 40°C / min or less. If the cooling rate is less than 20°C / min, sufficient quenching cannot be performed, and the tensile strength may decrease. If the cooling rate exceeds 40°C / min, additional equipment to accelerate the cooling rate is required, which increases manufacturing costs.
[0072] When a lubricant is used, a degreasing step of holding the compact at a temperature in the range of 400° C. to 700° C. for a certain period of time may be carried out before sintering in order to decompose and remove the lubricant.
[0073] The manufacturing conditions and equipment for the sintered body other than those described above are not particularly limited, and any desired ones can be applied.
[0074] (Heat treatment) The iron-based sintered body thus obtained may be further subjected to a heat treatment. By performing the heat treatment, the strength of the sintered body may be further increased. The heat treatment is preferably a treatment accompanied by quenching, and for example, strengthening treatments such as carburizing and quenching, bright quenching, high-frequency quenching, and carbonitriding heat treatment may be performed. In addition, the sintered body after quenching may be subjected to a recovery treatment for impact resistance such as tempering. The tempering temperature is preferably about 100 to 300°C.
[0075] The iron-based sintered body in one embodiment of the present invention can be obtained by pressurizing the iron-based mixed powder for powder metallurgy into a desired shape to form a molded body, sintering the molded body to form a sintered body, and sequentially subjecting the sintered body to carburizing, quenching, and tempering. EXAMPLES
[0076] The present invention will now be described in more detail with reference to examples. The following examples are intended to illustrate preferred embodiments of the present invention, and are not intended to limit the scope of the present invention.
[0077] An iron-based mixed powder for powder metallurgy was produced by the following procedure.
[0078] First, a water atomization method was used to prepare iron-based powders having the component compositions shown in Tables 1 to 3. The amounts of P and S contained as unavoidable impurities in the iron-based powders were P: less than 0.025 mass %, and S: less than 0.025 mass %.
[0079] The obtained iron-based powder was mixed with MoO as a Mo raw material powder. 3The MoO powder was added and mixed in a V-type mixer for 15 minutes. Then, heat treatment was performed in a hydrogen atmosphere to obtain the MoO 3 The powder was reduced to cause Mo to diffuse and adhere to the particle surfaces of the iron-based powder. The heat treatment was carried out at a temperature of 900° C. for 60 minutes.
[0080] After the heat treatment, the heat-treated body in which the particles were sintered together to form a mass was pulverized using a hammer mill and classified using a sieve with an opening of 180 μm, and the powder that fell under the sieve was collected to obtain a partially diffused alloyed steel powder. The amounts of C, O, and N contained as impurities in the partially diffused alloyed steel powder were C: less than 0.01 mass%, O: less than 0.20 mass%, and N: less than 0.05 mass%.
[0081] The alloying metal powders, graphite powder, and lubricant shown in Tables 1 to 3 were added to the obtained partially diffused alloyed steel powder, and mixed using a double-cone mixer to obtain an iron-based mixed powder for powder metallurgy. The graphite powder was added in an amount of 0.3 parts by mass per 100 parts by mass of the partially diffused alloyed steel powder and the alloying metal powder. Zinc stearate was used as the lubricant, and the amount added was 0.5 parts by mass per 100 parts by mass of the partially diffused alloyed steel powder and the alloying metal powder.
[0082] The apparent densities of the partially diffused alloyed steel powder, Cu powder, and Ni powder used were as shown in Tables 1 to 3. The apparent densities were measured in accordance with JIS Z 2504:2012.
[0083] Next, in order to evaluate the properties of the obtained iron-based mixed powder for powder metallurgy, a sintered body was produced using the iron-based mixed powder for powder metallurgy in the following manner.
[0084] The iron-based mixed powder for powder metallurgy was molded at a molding pressure of 588 MPa to obtain a rectangular solid-shaped compact of 10 mm x 10 mm x 55 mm. The weight of the obtained compact was measured, and the density of the compact was calculated by dividing the weight by the volume of the compact. The densities of the obtained compacts were as shown in Tables 1 to 3.
[0085] The obtained molded body was then placed in an RX atmosphere (N 2-32% by volume H 2 -24% CO by volume -0.3% CO by volume 2 ) (holding temperature 1130°C, holding time 20 minutes) to obtain a sintered body. The obtained sintered body was gas carburized (holding temperature 870°C, holding time 60 minutes) with a carbon potential of 0.8 mass%, and then quenched (temperature 60°C, oil quenching) and tempered (holding temperature 200°C, holding time 60 minutes). Carbon potential is an index that indicates the carburizing ability of the atmosphere in which steel is heated, and is expressed as the carbon concentration on the surface of the steel when it reaches equilibrium with the gas atmosphere at that temperature.
[0086] The density of the obtained sintered body was measured in accordance with JIS Z 2501. In addition, the tensile strength and impact value were measured to evaluate the strength and impact resistance of the sintered body. The tensile strength was measured by a tensile test specified in JIS Z 2241. The tensile test was performed at room temperature using a test piece with a parallel part diameter of 5 mm taken from the sintered body. The maximum stress before fracture measured in the tensile test was taken as the tensile strength. In addition, the impact value was determined by measuring the absorbed energy at room temperature in accordance with JIS Z 2242 and dividing the absorbed energy by the cross-sectional area of the test piece. The measurement results were as shown in Tables 1 to 3.
[0087] As can be seen from the results shown in Tables 1 to 3, in the examples where iron-based mixed powders for powder metallurgy satisfying the conditions of the present invention were used, the densities of the green bodies and sintered bodies were high, and the powder compressibility was excellent. Furthermore, in the examples where iron-based mixed powders for powder metallurgy satisfying the conditions of the present invention were used, sintered bodies having both high tensile strength and impact value were obtained. Specifically, the tensile strength was 1200 MPa or more, and the impact value was 13 J / cm. 2 As described above, according to the present invention, a sintered body having extremely excellent properties can be produced in a general production process in which the compaction pressure is less than 600 MPa. In contrast, in the example in which the iron-based mixed powder for powder metallurgy satisfying the conditions of the present invention was used, at least one of compressibility, strength, and impact resistance was inferior.
[0088] [Table 1]
[0089]
Table 2
[0090]
Table 3
Claims
1. An iron-based mixed powder for powder metallurgy, comprising a partially-diffused alloyed steel powder in which Mo is diffused and attached to the particle surfaces of the iron-based powder, and an alloying metal powder, The iron-based powder is Mn: 0.04% by mass or more and 0.15% by mass or less, Si: 0.01% by mass or more and 0.10% by mass or less, and The remainder of the composition is Fe and unavoidable impurities. The Mo content in the partially diffused alloyed steel powder is 0.20 mass% or more and 1.5 mass% or less, The apparent density of the partially diffused alloyed steel powder is 2.8 g / cm 3 3.6g / cm or more 3 is as follows: The alloying metal powder has an apparent density of 0.5 to 2.0 g / cm 3 Cu powder and apparent density: 0.5 to 2.0 g / cm 3 and with respect to the total mass of the partially diffused alloyed steel powder and the alloying metal powder, The amount of Cu powder added is 0 to 3.0 mass %, The amount of the Ni powder added is 0 to 3.0 mass%, and The iron-based mixed powder for powder metallurgy, wherein the total amount of the Cu powder and the Ni powder is 0.5 mass % or more.
2. 2. The iron-based mixed powder for powder metallurgy according to claim 1, wherein a ratio of a mass of said Ni powder to a total mass of said Cu powder and said Ni powder is 0.8 or less.
3. 3. An iron-based sintered body obtained by carburizing, quenching, and tempering a sintered body using the iron-based mixed powder for powder metallurgy according to claim 1 or 2.
Citation Information
Patent Citations
Alloy steel powder for powder metallurgy and its production
JP1984215401A
Low-alloy iron powder for sintering
JP1986295302A
High-strength alloy steel powder for powder metallurgy and its production
JP1988297502A
Alloy steel powder for powder metallurgy
JP1989142002A
Alloy powder for sintered alloy blending and manufacturing method of sintered alloy therewith
JP2014167141A